ECHOES AT THE EDGE: EXPLORING THE BOUNDARIES OF LISTENING - Nagarani, Dharmarajula; Venkateswarlu, Velpula (International Journal of Psychosocial Rehabilitation, 2019)
To be listening, according to Jean-Luc Nancy, is ‘is always to be on the edge of meaning’. How do we listen to a poem’s edge? To the end of the line? This essay thinks about line endings and how they invite our listening. It explores the acoustics, dynamics, and somatic experience of line endings in the works of a number of poets, including Alice Oswald, Kathleen Jamie, William Wordsworth, and Jen Hadfield. It draws on Nancy, Denise Levertov, and Rita Dove’s thinking about line endings, and offers a series of amplified close-listenings which open up wider thinking about how we read and experience poetry. This is part of a larger exploration of what it means to listen to a poem — to the sounds a poem remembers, to the sounds a poem makes — on the page, in the air, in the ear — but also to the spaces, to the gaps and pauses, to the white space at the end of a line.